2013
DOI: 10.1128/jvi.03486-12
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermodynamic Basis of Amprenavir/Darunavir and Atazanavir Resistance in HIV-1 Protease with Mutations at Residue 50

Abstract: Drug resistance occurs through a series of subtle changes that maintain substrate recognition but no longer permit inhibitor binding. In HIV-1 protease, mutations at I50 are associated with such subtle changes that confer differential resistance to specific inhibitors. Residue I50 is located at the protease flap tips, closing the active site upon ligand binding. Under selective drug pressure, I50V/L substitutions emerge in patients, compromising drug susceptibility and leading to treatment failure. The I50V su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…Previously, we showed that the I50V/A71V protease has decreased vdW interactions with the protease inhibitors APV and DRV compared with WT (0.61 and 1.98 kcal/mol, respectively), mainly due to the loss of a methyl group interacting with the sulfonyl moiety in APV/DRV (39). The coevolved I50V/A71V LP1′F and I50V/A71V PP5′L structures have more vdW contacts, and I50V/A71V RP4′S has more hydrogen bonds compared with WT WT complex.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we showed that the I50V/A71V protease has decreased vdW interactions with the protease inhibitors APV and DRV compared with WT (0.61 and 1.98 kcal/mol, respectively), mainly due to the loss of a methyl group interacting with the sulfonyl moiety in APV/DRV (39). The coevolved I50V/A71V LP1′F and I50V/A71V PP5′L structures have more vdW contacts, and I50V/A71V RP4′S has more hydrogen bonds compared with WT WT complex.…”
Section: Discussionmentioning
confidence: 97%
“…44 This was not the case for TPV, where a reduction in ΔΔH was reported for the same mutation. 44 Mutation A71V, which tends to appear together with I50V, 12 is known to compensate for the loss of viral fitness due to primary drug resistance-associated mutation. 83 An ITC study of I50V+A71V double mutant 12 suggested an increase in affinity toward ATV as a result of an increase in entropy which compensated the increase in enthalpy.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 99%
“…It also has been suggested to cause resistance toward Indinavir (IDV), 9,11 and at the same time, there is evidence pointing that this mutation has been associated with sensitivity toward Atazanavir (ATV) 12,13 and Tipranavir (TPV).…”
mentioning
confidence: 99%
“…WT NL4-3 HIV-1 protease had a Michaelis-Menten constant, Km, of 71 ± 7 M for cleaving this substrate, which was similar to that of I84V and V82I variants (66 ± 4 and 62 ± 4 M, respectively). The primary resistance mutation I50V is known to reduce catalytic activity, 31 and while I50V is still catalytically active, the Km value is beyond the limit of detection for this assay. A71V, a compensatory mutation that is far from the active site and almost always observed with I50V, restores the functionality to WT level (Km = 73 ± 9 M), as previously reported.…”
Section: Enzymatic Activity Of Protease Variantsmentioning
confidence: 99%
“…Mutations at I50 are often selected together with A71V mutation, which is distal from the active site but compensates for the loss of enzymatic fitness 30 . Thermodynamics and structural studies of DRV binding to I50V/L and A71V mutations have revealed significant loss of van der Waals (vdW) contacts between the inhibitor and protease underlying loss of binding affinity 31 .…”
mentioning
confidence: 99%